2003
DOI: 10.1093/toxsci/kfg076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Exposure to Aflatoxin B1 on DNA and RNA Adduct Formation in Rat Liver: Dose-Response and Temporal Patterns

Abstract: We studied the effects of intermittent exposure to aflatoxin B1 (AFB1) on hepatic DNA and RNA adduct formation. Fisher-344 male rats were fed 0.01, 0.04, 0.4, or 1.6 ppm of AFB1 intermittently for 8, 12, 16, and 20 weeks, alternating with 4 weeks of dosing and 4 weeks of rest. Other groups of rats were fed 1.6 ppm of AFB1 continuously for 4, 8, 12, and 16 weeks. Control rats received AFB1-free NIH-31 meal diet. AFB1-DNA and -RNA adducts were measured by HPLC with fluorescence detection. The data are presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
1
14
0
2
Order By: Relevance
“…Some phytobiotics act as growth promoters and others can neutralize the toxic effects of xenobiotics like AFB 1 [43,49,50]. The covalent bonding of AFB 1 -epoxide with DNA modifies the structure of the nucleic acid and biological activity, generating RNA and DNA adducts with potential mutagenic, carcinogenic and teratogenic characteristics [51]. …”
Section: Resultsmentioning
confidence: 99%
“…Some phytobiotics act as growth promoters and others can neutralize the toxic effects of xenobiotics like AFB 1 [43,49,50]. The covalent bonding of AFB 1 -epoxide with DNA modifies the structure of the nucleic acid and biological activity, generating RNA and DNA adducts with potential mutagenic, carcinogenic and teratogenic characteristics [51]. …”
Section: Resultsmentioning
confidence: 99%
“…Dietary exposure to carcinogens and mutagens depends on individual consumption patterns, which change with age, availability of food and lifestyle (64). Human and animal foods are commonly contaminated by aflatoxins during plantation, crop maturation, harvesting and storage.…”
Section: Food Regulationmentioning
confidence: 99%
“…Sotomayor et al (7) suggested that binding of aflatoxin B 1 (AFB 1 ) to hepatic DNA in rat liver is a linear function of the dose, regardless of the way that it is administered. The doseresponse relationship for RNA adducts depends on the length of the no-dosing cycles and the turnover rate of RNA.…”
mentioning
confidence: 99%